2003
DOI: 10.1001/archpsyc.60.9.904
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Family-Focused Psychoeducation and Pharmacotherapy in the Outpatient Management of Bipolar Disorder

Abstract: Combining family psychoeducation with pharmacotherapy enhances the postepisode symptomatic adjustment and drug adherence of bipolar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
348
2
32

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(402 citation statements)
references
References 90 publications
11
348
2
32
Order By: Relevance
“…A 2-year followup showed continuation of treatment effect with FFT patients experiencing fewer relapses (35 vs 54%, hazard ratio = 0.38), longer survival intervals (74 vs 53 weeks, P = 0.003), greater medication adherence and greater reduction in mood symptoms. 91 Medication adherence mediated positive effects on mania symptoms but not depressive symptoms.…”
Section: Family-focused Treatmentmentioning
confidence: 98%
“…A 2-year followup showed continuation of treatment effect with FFT patients experiencing fewer relapses (35 vs 54%, hazard ratio = 0.38), longer survival intervals (74 vs 53 weeks, P = 0.003), greater medication adherence and greater reduction in mood symptoms. 91 Medication adherence mediated positive effects on mania symptoms but not depressive symptoms.…”
Section: Family-focused Treatmentmentioning
confidence: 98%
“…25 Family-focused therapy involves the patient and caregivers (parents or spouse) in up to 21 sessions of psychoeducation, communication skills training, and problem-solving skills training. 89 Two randomised controlled trials including symptomatic patients with bipolar I and II found that, in the 1-2 years after a manic, mixed, or depressive episode, patients with bipolar disorder who received familyfocused therapy and pharma cotherapy had 30-35% lower rates of relapse and rehospitalisation and less severe symptoms than did patients in case manage ment 28 or equally intensive individual treatment. 63 Two randomised controlled trials in paediatric populations-one in adolescents (aged 12-18 years) with bipolar disorder 64 and one in children and adolescents (aged 9-17 years) with depression or hypomania with a first degree relative with bipolar disorder 65 -found that children and adolescents who received familyfocused therapy and pharmacotherapy recovered more rapidly from depressive episodes (HR 0·37-0·54) than did children and adolescents in brief psychoeducation and pharmacotherapy.…”
Section: Family-focused Therapymentioning
confidence: 99%
“…Responses to stressful events 23,24 Negative events are associated with depressive episodes; goal attainment events are associated with manic episodes; psychosocial treatments can modulate responses to stress High expressed emotion and negative family interactions 23,25,26 Crucial attitudes in caregivers and negative verbal interactions between caregivers and patients associated with greater likelihood of recurrence; family-focused therapy enhances family communication and is associated with reduction in mood symptoms Drug adherence [27][28][29] Psychoeducational treatments improve adherence to mood stabilisers, leading to lower likelihood of manic recurrence…”
Section: Psychosocial Variablesmentioning
confidence: 99%
“…A TCC com ênfase na educação sobre a doença e o tratamento, com reestruturação cognitiva e intervenções para solucionar os problemas, a rotina e melhorar distúrbios do sono, diminuiu os episódios depressivos, de mania e hipomania, mantendo o paciente eutímico por mais tempo. A terapia focada na família também melhora o curso da doença, diminuindo as crises depressivas e maníacas, além de oferecer maior proteção contra as recorrências de depressão (Otto et al, 2003).…”
Section: Adesão E Transtorno Bipolarunclassified